Replication Inhibitors Modulate Instability of an Expanded Trinucleotide Repeat at the Myotonic Dystrophy Type 1 Disease Locus in Human Cells - Yang, Zhi (The American Society of Human Genetics, 2003)
Gene-specific CTG/CAG repeat expansion is associated with at least 14 human diseases, including myotonic dystrophy type 1 (DM1). Most of our understanding of trinucleotide instability is from nonhuman models, which have presented mixed results, supporting replication errors or processes independent of cell division as causes. Nevertheless, the mechanism occurring at the disease loci in patient cells is poorly understood. Using primary fibroblasts derived from a fetus with DM1, we have shown that spontaneous expansion of the diseased (CTG)(216) allele occurred in proliferating cells but not in quiescent cells. Expansions were “synchronous,” with mutation frequencies approaching 100%. Furthermore, cells were treated with agents known to alter DNA synthesis but not to directly damage DNA. Inhibiting replication initiation with mimosine had no effect upon instability. Inhibiting both leading- and lagging-strand synthesis with aphidicolin or blocking only lagging strand synthesis with emetine significantly enhanced CTG expansions. It was striking that only the expanded DM1 allele was altered, leaving the normal allele, (CTG)(12), and other repeat loci unaffected. Standard and small-pool polymerase chain reaction revealed that inhibitors enhanced the magnitude of short expansions in most cells threefold, whereas 11%–25% of cells experienced gains of 122–170 repeats, to sizes of (CTG)(338)–(CTG)(386). Similar results were observed for an adult DM1 cell line. Our results support a role for the perturbation of replication fork dynamics in DM1 CTG expansions within patient fibroblasts. This is the first report that repeat-length alterations specific to a disease allele can be modulated by exogenously added compounds.